2016
DOI: 10.1021/acs.jpcc.6b11831
|View full text |Cite
|
Sign up to set email alerts
|

Bright Electrochemiluminescence Tunable in the Near-Infrared of Chiral Cationic Helicene Chromophores

Abstract: Cationic helicenes are ortho-fused polyaromatics which exhibit well-defined and stable helical conformations with original absorption and emission properties in the red to near-infrared spectral ranges. Herein, a selection of cationic [4] and [6]helicenes are studied for their electrochemical, fluorescence, and electrochemiluminescence (ECL) properties in acetonitrile solutions. Their photophysical and redox responses are drastically tuned by the introduction of auxochrome substituents at their periphery or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…The electrochemical properties of cationic [6]helicenes can be modulated by the nature of the heteroatoms (O, N) contained within the helical core or via the addition of peripheral substituents . The study on cationic [6]helicenes as a molecular redox probes for thin voltammetric films described earlier for the detection of cations is extended here to anions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical properties of cationic [6]helicenes can be modulated by the nature of the heteroatoms (O, N) contained within the helical core or via the addition of peripheral substituents . The study on cationic [6]helicenes as a molecular redox probes for thin voltammetric films described earlier for the detection of cations is extended here to anions.…”
Section: Resultsmentioning
confidence: 99%
“…The procedures for the preparation of dioxa + [6]helicene, dipropyl and dioctyl diaza + [6]helicenes (diaza + (C 3 ) 2 and diaza + (C 8 ) 2 , respectively) have been previously reported . These derivatives were synthesized in one step from a single common advanced synthetic intermediate (See Figure S1 for structural and synthetic information) . Regioselective bromination and nitration of the dioctyl derivative afforded the diaza + (C 8 ) 2 Br 2 and diaza + (C 8 ) 2 (NO 2 ) 2 moieties, respectively .…”
Section: Methodsmentioning
confidence: 98%
“…These derivatives, and novel didodecyl diaza + [6]helicene (diaza + (C 12 ) 2 ), were synthesized in one step from a single common advanced synthetic intermediate following reported procedures .…”
Section: Methodsmentioning
confidence: 99%
“…Other applications in electrochemiluminescence or ion transfer voltammetry were also reported for some [4]-and [6]helicene cationic dyes but focused only on racemic compounds. 282,283,284 In collaboration with Prof. Naaman, Lacour investigated aza [4]helicenium derivative [260][BF 4 ] as potential organic spin filter owing to the Chirality Induced Spin Selectivity (CISS) effect. 285,286 Using magnetic conductive probe atomic force microscopy (mCP-AFM) and magnetoresistance measurements set-ups, the authors showed that spin specific electron conduction is measured on chiral helicenium films with an opposite preferred spin for (P) and (M) enantiomers (Figure 38).…”
Section: Applications Of Carbocationic Azahelicenesmentioning
confidence: 99%